Forecasting Ukraine’s Macroeconomic Development in Conditions of Uncertainty: Expectations and Reality - Yashchenko, L. O.; Zhak, O. P.; Lysenko, R. S.; Rudenko, M. O. (Statistics of Ukraine, 2025)
Abstract. The evaluation of forecast accuracy is one of the key instruments for assessing the reliability and practical value of analytical models applied by various institutions in the field of macroeconomic forecasting. Under conditions of high volatility in both external and internal environments, the accuracy of forecasts acquires particular importance, as the adequacy and credibility of predictive estimates determine the soundness of strategic decisions in public economic policy, the effectiveness of monetary and fiscal regulation, the formation of investment expectations, and the identification of priorities for socio-economic development. This paper presents a comprehensive comparative analysis of forecasts produced by the Ministry of Economy, Environment and Agriculture of Ukraine (the Ministry of Economy), the National Bank of Ukraine (the NBU), and the International Monetary Fund (the IMF). The study utilizes data on key macroeconomic indicators, including nominal and real gross domestic product (GDP), consumer price index (CPI), nominal and real wages, as well as the dynamics of foreign trade operations (exports and imports of goods and services). The research involved systematization of forecast and actual values, calculation of mean relative errors (MRE) and mean absolute percentage errors (MAPE), and generalization of average deviation indicators. This approach made it possible to identify systematic tendencies – namely, the inclination to overestimate or underestimate actual values – and to assess the level of average forecasting error regardless of its direction. The results indicate that forecast accuracy significantly depends on the economic context. During periods of relative stability, forecasts by the NBU and the IMF tend to exhibit higher accuracy, while in times of crisis (2008–2009, 2014–2015, 2020–2021, 2022–2024), the Ministry of Economy’s projections remain the most reliable. Forecasts produced by the NBU account for monetary conditions, business and inflation expectations, and the transmission channels of monetary policy, which enables relatively precise reflection of inflationary trends, interest rate dynamics, and external balance. However, these forecasts are less responsive to short-term fluctuations in the real sector, structural changes in production, and fiscal factors, resulting in discrepancies between projected and actual trajectories of GDP and consumption – particularly under conditions of wartime economy. In contrast, IMF forecasts have a more global character and are largely based on standardized assumptions regarding the macroeconomic environment and external markets. This often leads to systematic deviations from actual figures, especially concerning inflation and external sector indicators, while the dynamics of domestic demand and supply are reflected in a simplified manner. Conversely, forecasts by the Ministry of Economy are more sensitive to internal factors of production, consumption, and investment. They better capture real GDP trends and demonstrate higher adaptability to structural shifts in the economy, making them an effective tool for developing and adjusting budgetary and socio-economic policy. The practical significance of this study lies in identifying the advantages and limitations of different methodological approaches and forecasting models. The findings provide a foundation for improving the national macro-forecasting system and for developing more adaptive evaluation tools capable of accounting for both structural imbalances and shock factors of economic development.